Growth And Yield Response of Two Pakchoi (Brassica Rapa L.) Varieties for Biofertilizer Application - Shafina, Najla Cherryl; Saylendra, Andree; Isminingsih, Sulastri; Sodiq, Abdul Hasyim (Jurnal Agroekoteknologi Terapan, 2025)
Pakchoy is one of the vegetables that is highly favored by the public. Consumer demand for pakchoy has increased in line with growing awareness of healthy living. The increase in pakchoy production needs to be supported by fertilization to maintain soil fertility. One effort to improve soil fertility is through the use of biofertilizers, which are a type of organic fertilizer containing microorganisms that can enhance or restore soil fertility. This study aims to determine the growth response and yield of two pakchoy varieties to the application of biofertilizer. The research was conducted from November 2024 to January 2025, located in the home yard at Warung Mangga Village, Pinang District, Tangerang City, Banten Province. The study used a Factorial Randomized Complete Block Design (RCBD) with two factors. The first factor had two levels: V1 = Nauli F1 variety and V2 = Flamingo variety. The second factor had five levels: H0 = no fertilizer, H1 = biofertilizer at 100 kg/ha, H2 = biofertilizer at 150 kg/ha, H3 = biofertilizer at 200 kg/ha, and H4 = NPK at 150 kg/ha (control). The observed variables included plant height, number of leaves, shoot fresh weight, root fresh weight, and root length. The results showed that the Nauli F1 pakchoy variety treated with a biofertilizer dose of 200 kg/ha exhibited the best response across all parameters: plant height, number of leaves, shoot fresh weight, root fresh weight, and root length. Keywords: Biofertilizer, Flamingo, Nauli F1, Varieties